Hubungan Perilaku Picky Eating dengan Status Gizi Anak Usia 1-3 Tahun di Posyandu Kelurahan Ciater Kota Tangerang Selatan - Sitti Latifah Faradiba Suaidy (2021)
Toddlers are children with an age range of 1-3 years, at this time toddlers are passive consumers. Problems with eating difficulties in toddlers can be an early source of nutritional and health problems for children. Picky eating behavior is one of the most common eating problems in toddlers. The impact of picky eating behavior can affect nutritional intake in children. This study aims to analyze the relationship between picky eating behavior and the nutritional status of children aged 1-3 years at the Posyandu, Ciater Village, South Tangerang City. The design used is descriptive analytic design with a cross sectional approach and carried out on 68 samples with simple random sampling method. Data was collected through google form using the Child Eating Behavior Questionnaire (CEBQ) and anthropometric measurements including height and weight. Pearson chi square analysis test obtained p value = 0.001 (< = 0.05) which means that there is a significant relationship between picky eating behavior and the nutritional status of children aged 1-3 years at the Posyandu, Ciater Village, South Tangerang City. Suggestions for further research are to conduct research with a wider population and use experimental research methods to improve nutritional status in children. Keywords: Toddler, Picky Eating Behavior and Nutritional Status